2011
DOI: 10.1017/s1368980011003077
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between dietary patterns and depression and anxiety in Chinese adolescents?

Abstract: Objective: To determine the association between major dietary patterns characterized by factor analysis and risk of depression and anxiety symptoms among adolescents. Design: Diet and symptoms of depression and anxiety were assessed in a crosssectional survey among students attending junior high school. Dietary patterns were derived from a self-reported FFQ, which consisted of thirty-eight items. Anthropometric measurements were also performed. Setting: Four junior high schools in Bengbu city, China. Subjects:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
123
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 56 publications
12
123
3
2
Order By: Relevance
“…Adherence to a 'processed food' dietary pattern was linked with increased risk, while a 'whole food' dietary pattern decreased the risk of depression in British middle-aged women (17) . Similar findings have also been reported from Norway (18) as well as from Chinese adolescents (19) . Almost all previous reports on dietary patterns and depression came from Western populations and we are not aware of any report in non-Western nations, particularly in Middle Eastern populations, where the dietary intakes are highly different from those in other parts of the world (20) .…”
supporting
confidence: 90%
“…Adherence to a 'processed food' dietary pattern was linked with increased risk, while a 'whole food' dietary pattern decreased the risk of depression in British middle-aged women (17) . Similar findings have also been reported from Norway (18) as well as from Chinese adolescents (19) . Almost all previous reports on dietary patterns and depression came from Western populations and we are not aware of any report in non-Western nations, particularly in Middle Eastern populations, where the dietary intakes are highly different from those in other parts of the world (20) .…”
supporting
confidence: 90%
“…Consistent with current literature, healthy dietary consumption in terms of lower levels of fruit, vegetable, fruit juice, and potato intake, and high levels of green salad consumption, had greater odds of poor mental health regarding depression, suicidal ideation, suicide attempts, and suicide plan, for the most part of Asians, Caucasians, and African Americans Weng et al, 2011). However, unexpectedly, mixed findings were displayed regarding greater carbonated soft drink and milk consumption.…”
Section: Discussionsupporting
confidence: 83%
“…On the one hand, there is convincing evidence that the dietary patterns of adolescents is one of the significant indicators of better mental health outcomes (Bakhtiyari, 2012;Estherlydia & John, 2009;Lien, 2007;Lien, Heyerdahl, Thoresen, & Bjertness, 2006;Oddy et al, 2009;Takaoka & Kawakami, 2013;Weng et al, 2011) in which healthy eating habits decreased the risk of depression, anxiety, and suicidality. Hence, healthy dietary patterns are considered one of the modifiable protective factors (McMartin, Jacka, & Colman, 2013) based on positive youth development and psychology.…”
Section: Constructing New Risk and Protective Factors To Build Resilimentioning
confidence: 99%
“…Some studies have suggested that an increase in carbohydrate-dense but nutrient-poor foods such as sweets, snacks, and fast food may be used to cope with negative mood and elevate mood by increasing brain serotonin levels (24). Regarding red meat consumption, the study found that a more healthy frequency of meat consumption (once a week) was associated with the highest happiness score and the lowest depressive scores, which was also found in a Scottish health survey (25).…”
Section: Discussionmentioning
confidence: 57%